A study of the feasibility of using low cost thick film tracks in the lower part of the microwave spectrum - Jakubowska, Małgorzata; Pitt, Keith (Видавництво Національного університету "Львівська політехніка", 2002)
Conventionally it is accepted that conductors for low microwave applications should meet a range of electrical and topographic criteria in order to perform correctly. These include a minimum thickness due to skin effects, smooth track and substrate surfaces and rectilinear geometry. The metal must also be very dense and uniform and have the highest possible electrical conductivity. As a result, photolithographically defined gold tracks are preferred and may be made in either thick or thin film.
Keywords: Thick film conductors; microwave properties; microwave measurements; quality control